PEMETAAN SARANA DAN PRASARANA OBJEK WISATA DI DESA GIRI, KABUPATEN GRESIK SEBAGAI DESA WISATA RELIGI: PEMETAAN SARANA DAN PRASARANA OBJEK WISATA DI DESA GIRI, KABUPATEN GRESIK SEBAGAI DESA WISATA RELIGI - Laily Endah Fatmawati; Nurul Rochmah (Program Studi Arsitektur Institut Teknologi Nasional (ITN) Malang, 2022)
Indonesia is a country that has a variety of cultures, ethnicities, and natural resources which are one of the foundations of the Indonesian state making this diversity the basis for developing tourism objects. Various riches and cultural diversity that the Indonesian state has, there is one area that has a wealth of religious culture, namely in Giri Village, Gresik Regency. The problem that will be studied in this research is the mapping of facilities and infrastructure owned by religious cultural tourism in Giri village, Gresik Regency. The purpose of this study is to present information in the form of a map of facilities and infrastructure on the availability of the needs of tourists who come to the location. The data collection method used in this study is the method of documentation and observation. The documentation method is used to find out information in the form of notes to obtain secondary data, namely administrative limits, number of visitors, and the road network around the tourist village. The next method, namely the observation method, is carried out by identifying conditions in the field to obtain data on object points astronomically. The data analysis was carried out using descriptive analysis to provide an overview to the community and local government regarding the mapping to be carried out. The expected result of this mapping is a thematic map in the form of a blueprint of an administrative map and a map of pre-tourism facilities mapped using the ArcMap program. The conclusions that will be obtained from this survey and mapping will be used to determine the availability of facilities and infrastructure in sunan giri religious tourism in Giri Village, Gresik Regency, East Java.